An Empirical Comparison between CAPM and D-CAPM in A Malaysian Context - Teh, Kwong Yew (2011)
The purpose of this study is to conduct an empirical test on the D-CAPM of Estrada (2002) alongside the traditional CAPM. This is because the variance measure has been severely criticized and researchers are turning to downside risk measures for possible alternatives. The D-CAPM has been suggested to be conceptually superior to the CAPM and few earlier downside risk asset pricing models. It is superior in the sense that the semivariance replaces the variance in the D-CAPM. Variance considers extreme positive and negative returns as equally undesirable but the semivariance penalizes negative returns heavier than positive returns. Hence, semivariance is more consistent with the fact that investors only dislike downside volatility but not huge positive returns. Secondly, straightforward portfolio optimization algorithm cannot be produced for earlier downside risk asset pricing models. As for the D-CAPM, Estrada (2008) managed to produce a heuristic closed-form solution to portfolio optimization that can overcome problems faced by earlier models. The empirical tests of this study are based on time-series data of the Malaysian stock market obtained from Datastream. Nevertheless, the empirical results show that the CAPM and D-CAPM are empirically indistinguishable. Neither model can be recommended as an appropriate and valid asset pricing model for the Malaysian stock market.